Adopsi QRIS pada UMKM di Desa Sidowayah sebagai Inovasi Pembayaran Digital - Ayundasari Ayundasari; Nawiroh Vera; Artyasto Jatisidi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This community service program aims to improve digital literacy and QRIS adoption among Micro, Small, and Medium Enterprises (MSMEs) in Sidowayah Village, Klaten Regency. The program was implemented from August to November 2025 through the MBKM Diktisaintek Berdampak program, with door-to-door mentoring, QRIS registration assistance, and post-program monitoring. This study used the Diffusion of Innovation Theory and the Integrated Technology Acceptance and Use Theory (UTAUT) to understand the factors influencing technology adoption. The results showed that 5 out of 10 targeted MSMEs were able to adopt QRIS, especially the culinary sector, which had the highest adoption rate due to the need for fast transactions and increasing demand for digital payments from customers. The program also faced several challenges, including limited internet connectivity, low digital literacy, and psychological barriers such as fear of making technical errors. However, intensive mentoring in the community has been shown to increase MSMEs' confidence in using digital payment systems. This program demonstrates that collaborative and sustainable mentoring can facilitate the digital transformation of rural MSMEs and empower the community economy